Physicochemical analysis and application of sardinella fimbriata-derived hydroxyapatite in toothpaste formulations - Ayub Irmadani Anwar; Muhammad Ruslin; Erni Marlina; H Hasanuddin (BMC Oral Health)
Abstract Background Toothpaste contains hydroxyapatite is a natural substance derived from fish bones. This study examines the physicochemical process of natural hydroxyapatite, conducts organoleptic testing, and assesses the homogeneity of Fringescale sardinella (Sardinella fimbriata) fish bone in toothpaste formulations. Method The study employed laboratory experimental research in September 2021. The calcination technique was employed to acquire a calcium precursor to produce natural hydroxyapatite powder derived from the bones of Sardinella fimbriata fish. X-ray fluorescence (XRF) was investigated to analyze the element calcium (Ca)—the morphological evaluation involved using an X-ray diffractometer (XRD) to evaluate the crystallinity. Toothpaste was formulated using natural hydroxyapatite as an abrasive, with different concentrations of CaCO3: F0 (0%), F1 (30%), F2 (40%), and F3 (50%). The toothpaste formulation was evaluated by a sensory assessment conducted on ten persons. The toothpaste’s attributes were evaluated for consistency, thickness, acidity level, foam generation, stability, and overall preference. Results The calcium oxide content in fish bones was 60.25 m3/m%. The XRD of the natural fish bone hydroxyapatite compound has a crystallinity of 82.9%. The average hedonic test liked each toothpaste formula, but the F3 formula was preferred in color, aroma, taste, and texture. Conclusion Hydroxyapatite extracted from Sardinella fimbriata fish bone can be incorporated into toothpaste formulated with F3, which includes a 50% hydroxyapatite concentration.